(untitled) (Journal of Parents and Teachers, 1996)
Reading is fundamental in early childhood education, but many children choose to watch television instead of reading. The traditional teaching approach that does not promote a love of literature is questioned and strategies are suggested to encourage interest in books. A recent book that reflects on these aspects is also mentioned.